2015
DOI: 10.1007/s00340-015-6166-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of aluminum samples in He ambient gas at different pressures in a thick LIBS plasma

Abstract: radioactive, high temperature, toxic materials) [19][20][21][22][23][24][25], industry [26][27][28][29][30][31], architecture, medical (noninvasive study of human teeth and hair, diagnosis of cancer tissue, DNA analysis) [32][33][34][35][36][37], military and civil security (detection of explosive material and biological weapons) [38][39][40][41][42][43]. Most of these applications are investigated under the condition of earth's atmosphere (i.e., at 760 Torr in air atmosphere) in order to determine the selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…5a in gate delay time of 200 ns. The emission lines from Al samples and the self-absorption effect of Al lines have been investigated by experimental analyses of LIBS spectra in some papers, 40,41 which demonstrate the corresponding measured spectral lines in this study. The spectral parameters of different observed lines of Al sample are listed in Table 3.…”
Section: Comparison Of Aluminum Sample In Air and Watersupporting
confidence: 55%
“…5a in gate delay time of 200 ns. The emission lines from Al samples and the self-absorption effect of Al lines have been investigated by experimental analyses of LIBS spectra in some papers, 40,41 which demonstrate the corresponding measured spectral lines in this study. The spectral parameters of different observed lines of Al sample are listed in Table 3.…”
Section: Comparison Of Aluminum Sample In Air and Watersupporting
confidence: 55%
“…Finally, it should be noted that different parameters such as laser features (its wavelength [42], double or single pulse scheme [33,43], energy [34], and pulse duration [42]), ambient gas condition (the nature and its pressure [42,44]) and measurement device circumstance (delay time [8,34], gate width, and exposure time), and the sample characteristics (metal and biological cases) could affect the amount of self-absorption as well. The details of these effects can be studied in the related references.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that ambient gas components can influence plasma evolution. 13,14 During plasma evolution, the particles at the plasma front are subjected to a pressure gradient directed towards the sample surface and move towards it. In this process, a portion of the ambient gas is entrained into the plasma and becomes part of it, accompanied by an energy exchange.…”
Section: Introductionmentioning
confidence: 99%